History and Development of Clergy Training in Poland - Pawlina, Krzysztof (Verbum Vitae, 2023)
Among the many issues related to priesthood, questions often arise about how the Church prepares pupils/students for priestly service, what this formation involves and who is responsible for it. The article attempts to answer these questions from a historical perspective. It begins by presenting the idea of seminary life and the beginnings of the institution of theological seminaries. Then it discusses the decision of the Council of Trent, which obliged the Church to establish theological seminaries in all dioceses. The next stage in the education of the clergy was introduced by the document of the Second Vatican Council, Optatam Totius, which defines the nature and mission of a priest. It obliged local churches to develop their own Ratio Fundamentalis Institutionis. The Polish Ratio Fundamentalis drew its inspiration from this document. The analysis of the new Ratio for Polish seminaries developed in 2021 concludes the latest stage in the history of clergy formation.